Local Government Finance: It’s Relationship to the Socio-Economic Development in the Municipalities of Northern Samar, Philippines - Aducon, Ricabeth Anabe (JPAIR Multidisciplinary Research, 2019)
Local government units are recognized as viable organs for the performance of local functions; they are challenged to use their limited resources for delivering better services. Hence, the grant of local fiscal autonomy is considered necessary for the effective local government system and to achieve the objective of alleviating the economic conditions of the locality and efficient delivery of essential services to the populace. This paper has examined the financial management skills of local chief executives and the local government finance regarding social services, economic services and socioeconomic development in the twenty-four municipalities of Northern Samar. It also looked into the significant relationship between the financial management skills and local government finance of the local chief executives. Questionnaire and interview guide were used, utilizing a descriptive correlation method of research. The analysis concludes that the local chief executives are much skilled in financial management, have a high level of performance in local government finance in terms of social and economic services while an average level of performance in terms of socioeconomic development, it was also shown that the financial management skills of the local chief executive are related to local government finance.